Discussion of Professional Responsibilites-An Empirical Suggestion - Davidson, H. Justin (Journal of Accounting Research, 1966)
Before commenting on Carl Devine's paper, I want to take this opportunity to comment on the Conference on Empirical Research in Accounting. I am extremely pleased that research practitioners in accounting have finally discovered numbers. Both theory and practice in accounting are complicated. It seems to me that both require heavy doses of logic in analyzing the alternatives and consequences involved in the problems and issues we face. Both require sound evidence that measures those alternatives and consequences. Finally, both theory and practice require value judgments about those measured results. Unfortunately, I think that we within the accounting profession have too often applied logic and value judgments and ignored the evidence and facts. Further, I believe that this conference, with its focus on evidence, is one of the most healthy and significant developments that have taken place in accounting in many years. Although none of the papers presented here may shake the foundations of the accounting world, I believe that, ten years hence, the cumulative effort of many such empirical investigations will have radically changed the nature of the accounting profession's thought. Let me turn now to Carl Devine's paper. My first comment concerns simulation. Carl Devine comments on Neil Churchill's research involving simulation of the audit situation. He questions whether the coercive influence of auditors on employees under the stress of job security and other such influences is simulated accurately by graduate students involved in small-stake decision games. This is a relevant question which should be raised about any research involving simulation. Similarly, it must be raised about Professor Devine's research. How accurately does